2011
DOI: 10.1007/s00300-010-0954-1
|View full text |Cite
|
Sign up to set email alerts
|

Southernmost records of bottlenose dolphins, Tursiops truncatus

Abstract: Bottlenose dolphins (Tursiops spp.) are cosmopolitan animals widely distributed in waters of both hemispheres. The taxonomy of Tursiops has long been controversial, with over 20 specific names being published, and subspecies and inshore/offshore forms being proposed. In the southwestern South Atlantic, subspecies T. truncatus truncatus and T. truncatus gephyreus were proposed for specimens along the coasts of Brazil, Uruguay, and Argentina. Sightings of bottlenose dolphins are common along the coast of Argenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Bottlenose dolphins have been observed from Samborombón Bay (province of Buenos Aires) to the southern province of Chubut, although occasional records exist further south in the provinces of Santa Cruz and Tierra del Fuego (Goodall, 1989;Bastida et al, 2007;Goodall et al, 2011). The earliest record of bottlenose dolphins for this region was based on the capture of two individuals reported by Lahille (1908) in the La Plata River.…”
Section: Argentinamentioning
confidence: 99%
See 1 more Smart Citation
“…Bottlenose dolphins have been observed from Samborombón Bay (province of Buenos Aires) to the southern province of Chubut, although occasional records exist further south in the provinces of Santa Cruz and Tierra del Fuego (Goodall, 1989;Bastida et al, 2007;Goodall et al, 2011). The earliest record of bottlenose dolphins for this region was based on the capture of two individuals reported by Lahille (1908) in the La Plata River.…”
Section: Argentinamentioning
confidence: 99%
“…The common bottlenose dolphin (Tursiops truncatus Montagu, 1821), hereafter bottlenose dolphin, is a cosmopolitan species distributed throughout tropical and temperate coastal and pelagic waters, between 45°N and 54°S 1 (Goodall et al, 2011). Studies on this species in the Southwest Atlantic Ocean (SWAO) have intensified in the last two decades, albeit with irregular effort.…”
Section: Introductionmentioning
confidence: 99%
“…Cremer et al, 2009) and Argentina (Vermeulen and Cammareri, 2009;Goodall et al, 2011), also revealed that the genus Tursiops presents a more complex variation than a simple latitudinal differentiation in the SWAO.…”
Section: Taxonomymentioning
confidence: 98%
“…A comprehensive understanding of the taxonomic status and population structure of bottlenose dolphins in this region depends on a more detailed analysis of individuals from coastal and oceanic zones along different latitudes. In addition, for a complete understanding of taxonomy and stock discreteness of bottlenose dolphins in the southernmost areas of Argentina (between 53°S and nearly 55°S), future genetic studies on both ocean basins off South America will be necessary, since a connection between Atlantic and Pacific animals is possible via the southern fjords and channels of South America (Olavarria et al, 2010;Goodall et al, 2011).…”
Section: Taxonomymentioning
confidence: 99%
See 1 more Smart Citation